Rancang Bangun Mesin Laser Engraver and Cutter Untuk Membuat Kemasan Modul Praktikum Berbahan Akrilik - Aris Eko Saputro; Mochammad Darwis (UPT Laboratorium Terpadu, Universitas Diponegoro, 2020)
In the competence of vocational institution, lecturers, students and PLP staff are expected to make their own appropriate equipment. An educational laboratory as a place to provide adequate practice and supporting equipments. Equipment or innovations that are designed must be packaged in an attractive form as a prototype of a product. As for the research and or as a practical tool in the laboratory. The packaging also serves to protect the device made and increase its life time. Usually the material used to make a casing material is acrylic. The thicker the acrylic, the more difficult it is to make. Laser engraver or laser cutter as a solution to facilitate the manufacture of casings that made from acrylic. User will create a two-dimensional design using a program, such as Inkscape. Then the design is saved or changed into gcode. The resulting gcode file is then sent to the laser engraver to make the design. The power of the laser head used, will determine the thickness of the acrylic to be cut. In this research, 2 mm thick acrylic was tested using a 15W laser diode module.